Efficacy of Plasma Exchange in Myasthenia Gravis Following Long COVID in a Resource-Limited Context: A Case Report - Bihariesingh-Sanchit, Rosita; Bansie, Rakesh; Ma, Rocade; Veenbergen, Sharon; Diavatopoulos, Dimitri Adriaan; Jonge, Marien Isaäk de; Nierich, Arno (Brazilian Journal of Case Reports, 2025)
This case report describes the development of myasthenia gravis (MG) in a 71-year-old male patient with long COVID and outlines the management of an MG exacerbation. The patient exhibited significant symptoms, including fatigue, cognitive impairment, dysphagia and dysarthria. Although transient improvement was observed after treatment with pyridostigmine, the patient's condition later worsened, with marked axial and buccopharyngeal weakness. Symptom relief was finally achieved with plasmapheresis using a low-volume crossflow gravity-driven method. This case highlights the potential long-term impact of COVID-19 on autoimmune disorders such as MG and emphasizes the need for vigilance in managing post-COVID neurological complications.